2012
DOI: 10.1007/s00216-012-6195-0
|View full text |Cite
|
Sign up to set email alerts
|

Angle-dependent resonance of localized and propagating surface plasmons in microhole arrays for enhanced biosensing

Abstract: The presence of microhole arrays in thin Au films is suited for the excitation of localized and propagating surface plasmon (SP) modes. Conditions can be established to excite a resonance between the localized and propagating SP modes, which further enhanced the local electromagnetic (EM) field. The co-excitation of localized and propagating SP modes depends on the angle of incidence (θ(exc)) and refractive index of the solution interrogated. As a consequence of the enhanced EM field, enhanced sensitivity and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…This coupling has been already shown experimentally and demonstrated for samples with a glass substrate with a SiO2 spacer between gold nanodisks and gold film [35,42]. The possibility to have the excitation of localized and propagating surface plasmon modes can be also obtained with microhole arrays in thin Au films [43]. EFs increase from 633 nm to 785 nm by a factor around 10, which is in good agreement with previous results showing the importance of the excitation wavelength as function of the diameter [44] for disks.…”
Section: Quantification Of Enhancement Factor and Discussionmentioning
confidence: 74%
“…This coupling has been already shown experimentally and demonstrated for samples with a glass substrate with a SiO2 spacer between gold nanodisks and gold film [35,42]. The possibility to have the excitation of localized and propagating surface plasmon modes can be also obtained with microhole arrays in thin Au films [43]. EFs increase from 633 nm to 785 nm by a factor around 10, which is in good agreement with previous results showing the importance of the excitation wavelength as function of the diameter [44] for disks.…”
Section: Quantification Of Enhancement Factor and Discussionmentioning
confidence: 74%
“…In addition, the authors could adjust the array dimensions and the thickness of the gold layer for resonance tuning. Large-scale gold microhole and nanohole arrays as well as silver nanocave arrays have also been fabricated and demonstrated for highly sensitive refractive index sensing [101][102][103][104]. Dou et al reported a simple and scalable colloidal lithography technology for fabricating gold nanodonuts, which demonstrated a high SPR sensitivity of ~758 nm/RIU [105].…”
Section: Spr Sensing With Nanostructure Arraysmentioning
confidence: 99%
“…110,108 This tunability for a particular application of interest allows for dramatic increases in SPR sensitivity. 107,[118][119][120] Although the tunability of such nanoarrays in gold is limited to the NIR and longer wavelength region of the visible (i.e., ∼500 nm or greater), a variation of these nanoslit and nanohole arrays, known as nanotriangle arrays [see Fig. 8(f)], 107 has demonstrated the ability to further expand the range of LSPR wavelengths achievable simply by altering the structure.…”
Section: Recent Advances In Surface Plasmonmentioning
confidence: 99%